2019
DOI: 10.3168/jds.2018-15109
|View full text |Cite
|
Sign up to set email alerts
|

A landscape of the heritability of Fourier-transform infrared spectral wavelengths of milk samples by parity and lactation stage in Holstein cows

Abstract: Fourier-transform near-and mid-infrared (FTIR) milk spectral data are routinely collected in many countries worldwide. Establishing an optimal strategy to use spectral data in genetic evaluations requires knowledge of the heritabilities of individual FTIR wavelength absorbances. Previous FTIR heritability estimates have been based on relatively small sample sizes and have not considered the possibility that heritability may vary across parities and stages of the lactation. We used data from ~370,000 test-day r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
2
13
1
Order By: Relevance
“…The authors have therefore proposed the use of infrared predictions at the population level for the genetic improvement of those traits that are difficult to measure. These findings are supported by the knowledge that many infrared wavelength absorbances of milk are heritable [ 45 , 46 , 47 ]. No information on the genetic background of beef absorbance spectra is available.…”
Section: Resultssupporting
confidence: 53%
“…The authors have therefore proposed the use of infrared predictions at the population level for the genetic improvement of those traits that are difficult to measure. These findings are supported by the knowledge that many infrared wavelength absorbances of milk are heritable [ 45 , 46 , 47 ]. No information on the genetic background of beef absorbance spectra is available.…”
Section: Resultssupporting
confidence: 53%
“…Wang and Bovenhuis (2019) estimated CH 4 emissions from milk IR spectra in 1508 dairy cows using cross-validation strategies, obtaining an R 2 cv of 0.49; however, when random block validation was used, the R 2 cv dropped to 0.01, demonstrating the importance of validation. Milk IR spectral wavelengths were confirmed to be heritable in over 200 000 cows (Rovere et al, 2019). This information opens up the possibility of using genetic covariance between informative spectral wavelengths and CH 4 emissions, if estimated.…”
Section: Improving the Selection Accuracy Of Ch 4 Emissionsmentioning
confidence: 74%
“…We directly estimated the heritability of every wavelength of the milk FTIR spectrum in Brown Swiss cows 48 and obtained values between 5 and 10% for the SWIR IR-B fraction, similar to those found here for the SWIR IR-B fraction of the beef spectrum. In a recent study 30 , we confirmed similar heritability values for the SWIR IR-B fraction of the milk spectrum in Holstein Friesian cows, and found that heritability was affected by parity and, especially, the cow’s lactation stage 29 , found an effect of herd on the absorbance of IR-B radiation (2000–2500 nm) by milk similar to or greater than in the present study, and a large genetic effect, more similar to that recorded for the absorbance of visible radiations by beef.…”
Section: Discussionmentioning
confidence: 93%
“…In using visible-infrared spectra for genetic improvement at the population level, it is clearly implicitly assumed that the absorbance of some wavelengths are heritable and correlated with the trait for selection, as was found for milk at the genetic 29 , 30 and genomic levels 31 . In the case of meat species, to our knowledge, there is no information on the genetics of meat absorbance spectra.…”
Section: Introductionmentioning
confidence: 99%